GAMBARAN DAYA HAMBAT MINYAK KELAPA MURNI DAN MINYAK KAYU PUTIH DALAM MENGHAMBAT PERTUMBUHAN Streptococcus mutans - Nova Rosdiana; Abdillah Imron Nasution (Dentistry Faculty, 2016)
Caries is infection disease and Streptococcus mutants (S. mutans) reported as the main agent of this disease. Some efforts has been reported to prevent of this disease, some of those efforts are with using herbal treatment such as virgin coconut oil and cajuput oil. The objective of this research is to find out inhibition of virgin coconut oil and cajuput oil on resisting S. mutans growth in in vitro. Method what used to find out S. mutans is cultured to TYS20B and TSB and then conducted inhibition test with diffusion in solid media. Data analysis develops using descriptive statistic. Results and discussion of this research are show differences of inhibition from materials test on growth of S. mutans with approximately of inhibition 7 mm for virgin coconut oil, 14 mm for cajuput oil, 15 mm for Chlorhexidine and 6 mm for aquades. The conclusion of this research is cajuput oil have larger inhibition than virgin coconut oil.Keywords : Caries, Streptococcus mutants, Inhibition, Virgin Coconut Oil, Cajuput Oil.